Analysis of the Impact of the Covid-19 Pandemic on Project Implementation Time in Batam City - Rabbito Tycoon Dartok; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
The pandemic that occurs is COVID-19 which has spread throughout the country to Indonesia including Batam City which has had a negative impact on construction work since the issuance of the PSBB regulations and health protocols, therefore it is necessary to conduct research to determine the factors that affect construction time management in Batam City in terms of material provision, labor and work methods. The research was carried out by distributing questionnaires to workers who worked in the Batam City construction project. Based on the questionnaire analysis, the percentage of the influence of the Covid-19 condition on construction time management in Batam city in terms of material procurement with a percentage of 50.16%, in terms of labor procurement with a percentage of 26%, and in terms of work methods with a percentage of 10.91%.